2023
DOI: 10.5507/bp.2023.002
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid neurofilament light chains and CXCL13 as predictive factors for clinical course of multiple sclerosis

Abstract: The aim of this study was to identify whether NfL and CXCL13 cerebrospinal fluid (CSF) concentrations at diagnostic lumbar puncture can predict the course of multiple sclerosis (MS) in terms of relapses, higher expanded disability status scale (EDSS) and magnetic resonance imaging (MRI) activity. Methods. We conducted a single-centre prospective observational cohort study at the MS center, University Hospital Ostrava, Czech Republic. CSF NfL (cNfL) and CXCL13 concentrations were examined (ELISA method) in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…In contrast, a recent study found CSF CXCL13 does not predict disease activity, measured by EDSS and MRI, in CIS/RRMS (Hradilek et al, 2023). In addition, it was also found that while CSF CXCL13 levels differed significantly between the MS and control groups in another study, no such differences were found between the RRMS and PPMS group in the stable phase of MS without relapse, despite these two subtypes of MS representing different stages of neurodegeneration (Iwanowski et al, 2017).…”
Section: Chemokine (C-x-c Motif) Ligand 13 (Cxcl13)mentioning
confidence: 79%
“…In contrast, a recent study found CSF CXCL13 does not predict disease activity, measured by EDSS and MRI, in CIS/RRMS (Hradilek et al, 2023). In addition, it was also found that while CSF CXCL13 levels differed significantly between the MS and control groups in another study, no such differences were found between the RRMS and PPMS group in the stable phase of MS without relapse, despite these two subtypes of MS representing different stages of neurodegeneration (Iwanowski et al, 2017).…”
Section: Chemokine (C-x-c Motif) Ligand 13 (Cxcl13)mentioning
confidence: 79%